The combination ovaprim with oksitosin toward the Ovulation and hatching rate of catfish (Mystus nigriceps) - Lumbantoruan, Ronal P.; Aryani, Netti; Heltonika, Benny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in Maret until Mey 2017 in Fish Hatchery and Breeding laboratory, Faculty of Fisheries and Marine Sciences University of Riau. The aim of this research was to determine the effect of combination ovaprim and oksitosin on ovulation and hatching of catfish (Mystus nigriceps). The method used in this research was an experimental method with Completely Randomized Design (CRD) with one factor, five treatments and three replications. The treatment used in this research was an injection of combination ovaprim and oksitosin i.e. P0 (100% ovaprim), P1 (25% oksitosin + 75% ovaprim), P2 (50% oksitosin + 50% ovaprim), P3 (75% oksitosin + 25% ovaprim), P4 (100% oksitosin (0,7 ml/kg). The results showed that the best in treatment combination ovaprim and oksitosin (P3 = 75% oksitosin + 25% ovaprim) which produce latency (6.03 hours), total eggs stripping (276 eggs/gr broodstock), Ovi Somatic Index (7.9 %), egg diameter increment (0.037 mm), egg maturity increment (7,6 %), fertilate rate (36%), hatching rate (52%), and survival rate of 5 days (61%).Keywords : Ovaprim, Oksitosin, Ovulation, and catfish (Mystus nigriceps)